Labour Law = قانون العمل. (2025)
Definitions and General provisions -- 2. Individual Labour Relationships -- 3. Vocational Guidance And Training -- 4. Collective Labour Relationships -- 5. Vocational Safety and Health and Ensuring Labour Environment Security